Evaluation of Human Enamel Surfaces Treated with Theobromine: A Pilot Study - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
Purpose: The objectives of this in-vitro study were to investigate the effect of theobromine, which is the principle xanthine species in Theobroma cacao, at two concentrations on the surface hardness and topography of human enamel. Materials and Methods: Twenty-four freshly extracted human third molars were collected and stored in distilled water with 0.1% thymol solution at room temperature prior to the experiments. The enamel specimens were treated with one coat of theobromine at two concentrations (100 mg/l or 200 mg/l in distilled water) for 5 min. Enamel surfaces in the control group received no theobromine. They were then kept in distilled water for 1 week and subjected to SEM analysis. The specimens were demineralised by storing them in acidic hydroxyethylcellulose for three days. After baseline microhardness measurements, they were incubated either in 100 or 200 mg/l theobromine for 5 min. The control group was kept in distilled water. After washing the specimens under distilled water, they were kept in a remineralising solution for 18 h. Microhardness of the enamel surface was initially determined for each specimen before artificial demineralisation. After demineralisation, the experimental groups were incubated in 100 mg or 200 mg theobromine and control-group specimens were placed in remineralising solution. Results: Enamel surfaces of the untreated control group presented a generally smooth and slightly hummocky surface with small lines of pits. Specimens treated with theobromine showed differences between the two concentrations. The group treated with 200 mg/l solution for 5 min showed a greater quantity of globules on enamel than did specimens treated with 100 mg/l solution. Conclusion: As shown by the microhardness values, a consistent and remarkable protection of the enamel surface was found with the application of theobromine.
Keywords: enamel; fluoride; SEM; Theobroma cacao; theobromine; NEWBORN RATS; IN-VITRO; 1ST MOLARS; REMINERALIZATION; DEMINERALIZATION; INHIBITION; CHOCOLATE; INVITRO; EXTRACT; LESIONS